Injury and Treatment Characteristics of Sport-Specific Injuries Sustained in Interscholastic Athletics: A Report From the Athletic Training Practice-Based Research Network. (January 2015) - Lam, Kenneth C.; Snyder Valier, Alison R.; Valovich McLeod, Tamara C.
Background: The inclusion of clinical practice factors, beyond epidemiologic data, may help guide medical coverage and care decisions. Hypothesis: Trends in injury and treatment characteristics of sport-specific injuries sustained by secondary school athletes will differ based on sport. Study Design: Retrospective analysis of electronic patient records. Level of evidence: Level 4. Methods: Participants consisted of 3302 boys and 2293 girls who were diagnosed with a sport-related injury or condition during the study years. Injury (sport, body part, diagnosis via ICD-9 codes) and treatment (type, amount, and duration of care) characteristics were grouped by sport and reported using summary statistics. Results: Most injuries and treatments occurred in football, girls' soccer, basketball, volleyball, and track and field. Sprain or strain of the ankle, knee, and thigh/hip/groin and concussion were the most commonly documented injuries across sports. The injury pattern for boys' wrestling differed from other sports and included sprain or strain of the elbow and neck and general medical skin conditions. The most frequently reported service was athletic training evaluation/reevaluation treatment, followed by hot/cold pack, therapeutic exercise, manual therapy techniques, electrical stimulation, and strapping of lower extremity joints. Most sports required 4 to 5 services per injury. With the exception of boys' soccer and girls' softball, duration of care ranged from 10 to 14 days. Girls' soccer and girls' and boys' track and field reported the longest durations of care. Conclusion: Injury and treatment characteristics are generally comparable across sports, suggesting that secondary school athletic trainers may diagnose and treat similar injuries regardless of sport. Clinical Relevance: Subtle sport trends, including skin conditions associated with boys' wrestling and longer duration of care for girls' soccer, are important to note when discussing appropriate medical coverage and care.